The Impact of Willingness to Engage in NeWOM and Brand Attitudes on Purchase Intention Mediated by Company Mitigation Responses: A Case Study of The Energy Drink in Central Java - Endwien Hersetyawati; M Arief; Asnan Furinto; Hardijanto Saroso (Journal of International Conference Proceedings (JICP), 2021)
The aims of this study were to determine the impact of willingness to engage in negative eWOM from and brand attitudes on purchase intention of Joss extra energy drink products mediated by mitigation responses of companies in Central Java. The method in this is descriptive and verification. This study used a purposive random sampling technique with a total sample of 167 respondents. The results of this study indicate that the Brand Attitude variable has nonsignificant effect on Repurchase Intention, the negative brand experience sharing (NBES) variable has nonsignificant effect on engaging in NeWOM, the negative electronic review (NER) variable has a significant effect on engaging in NeWOM, the variable involved in NeWOM has a significant effect on Brand Attitude, the variables involved in NeWOM have no significant effect on Repurchase Intention, and the CMR variable has not been proven to be successful in mediating the relationship between engaging in NeWOM and Repurchase Intention. This study also contributes to the meaning of strategic management, by empirically proving the importance of mediation of social networking sites and company mitigation responses variables and their role in influencing NBES and negative electronic reviews, negative electronic word of mouth on repurchase intention. The managerial implications to determine behavior and actions in assessing the performance of the company to seek the efforts made in dealing with the negative impact of NeWOM.